Evaluate the following expression given the function.
problem: h(x) = -2
solution: -2 = 12/x.
1/12 * -2 = 12/x *1/12 (mulitply both sides by 1/12 to get x by itself.
-2/12 = 1/x
-1/6 = 1/x (simplified -2/12)
I don't think this is right. Can you explain how to get the 'x' out of the denominator?
don't be scared by that x. It's juts a denominator. To get rid of it, multiply both sides by x.
Now, to find x when h = -2, just do what you did:
12/x = -2
now just multiply by x:
12 = -2x
x = -6posted by Steve
Thanks! That was so much easier :).posted by Alexis